2019
DOI: 10.1002/jper.19-0049
|View full text |Cite
|
Sign up to set email alerts
|

Compressive force‐induced autophagy in periodontal ligament cells downregulates osteoclastogenesis during tooth movement

Abstract: Background Autophagy has recently emerged as a protective mechanism in response to compressive force and an important process in maintenance of bone homeostasis. It appears to be involved in the degradation of osteoclasts, osteoblasts, and osteocytes. The aim of this study was to investigate the role of compressive force‐induced autophagy in periodontal ligament (PDL) cells in regulating osteoclastogenesis of orthodontic tooth movement (OTM). Methods An OTM model and compressive force on PDL cells were employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 47 publications
2
32
1
Order By: Relevance
“…The results of the present study suggested that cementocytes may participate in the modulation of the force-related osteoclast differentiation via the Wnt/β-catenin signaling pathway. These results are consistent with those of previous studies, where animal models have been demonstrated to exhibit root resorption and bone remodeling under compression (53,54). Other in vitro studies have also indicated that mechanoreceptor cells, including PDLs and osteocytes, detected forces and activated an intercellular signaling cascade that ultimately results in bone and tooth resorption (11,55,56).…”
Section: Discussionsupporting
confidence: 92%
“…The results of the present study suggested that cementocytes may participate in the modulation of the force-related osteoclast differentiation via the Wnt/β-catenin signaling pathway. These results are consistent with those of previous studies, where animal models have been demonstrated to exhibit root resorption and bone remodeling under compression (53,54). Other in vitro studies have also indicated that mechanoreceptor cells, including PDLs and osteocytes, detected forces and activated an intercellular signaling cascade that ultimately results in bone and tooth resorption (11,55,56).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have showed that autophagy is regulated in specialized mechanosensitive cells, such as nucleus pulposus cells (Ma et al, 2013), podocytes (Li et al, 2016), and skeletal muscle cells (Teng et al, 2011). In current study, autophagy was activated in PDLSCs in response to compressive stress, consistent with the recent preliminary study (Chen et al, 2019). Autophagy is a form of endogenous defense mechanism to maintain cellular homeostasis and prevent mechanical damage of environmental change (Mizushima and Levine, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…However, it remains largely unknown about the role of autophagy in periodontal ligament under orthodontic compressive force. Recent study preliminarily found that autophagy is increased in periodontal ligament fibroblasts under biomechanical loading (Chen et al, 2019;Memmert et al, 2019). However, the precise mechanism by which the autophagy is regulated at the compressed area during tooth movement remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in this tissue we find variable aspects of periodontal remodeling that can be studied in the context of osteoimmunology, activation of specific internal molecular mechanisms (e.g., cell signaling, mechanotransduction, autophagy), or alteration of the ECM features. [25,26] Each of these processes is controlled by a dynamic interaction between principal cellular elements of the PDL that includes osteoblasts, fibroblasts, cementoblasts, and fiber-like ECM. All together, these components are crucial for adjacent alveolar bone formation and regeneration into functional moieties.…”
Section: Molecular Mechanisms Of Periodontal Remodeling and Orthodontmentioning
confidence: 99%